Team-based strategic planning : a complete guide to structuring, facilitating, and implementing the process - Fogg, C. Davis (American Management Association New YorkUS, 1994)
Seeks to guide internal planners, facilitators, consultants etc.in making the strategic planning process work. Explains how to structure an efficient planning process; reviews the practical organizational, and other techniques and skills needed; describes how to use teams; looks at the role of management and leadership; discusses how and when to involve various levels of the organization; and describes useful techniques. Refers to actual companies to illustrate aspects of the process. Provides needed hands-on tools including: a strategic change process model; cue cards and flow charts; and a suggested list of contents of the planning manual.